Drying in newly intermittent rivers leads to higher variability of invertebrate communities. (30th December 2020) - Crabot, Julie; Polášek, Marek; Launay, Bertrand; Pařil, Petr; Datry, Thibault
Abstract: Aquatic invertebrate communities inhabiting intermittent rivers that are characterised by recurrent drying events (flow cessation or complete disappearance of surface water) often show rapid recovery upon flow resumption. Such rapid recovery is possible thanks to specific resistance and resilience traits that species adapted to river drying often exhibit. However, differences in community response to drying can be expected between historically drying (HD) networks—those IRs with a long history of flow intermittence—and recently drying (RD) networks, where drying is a novel, often human‐induced, phenomenon. The invertebrate species found in RD networks may lack the adaptations that are known to facilitate quick community recovery upon rewetting and could thus be dramatically affected by drying. Unfortunately, the responses of aquatic communities in RD networks are still poorly explored, limiting our capacity to predict and mitigate future biodiversity changes. Here, we compared the responses of aquatic invertebrate communities to drying in nine pairs of intermittent and perennial river reaches from HD networks across France and nine pairs from RD networks across the Czech Republic. Using both taxonomic and functional perspectives, differences in α‐ and β‐diversity patterns between perennial and intermittent sites were evaluated separately for HD and RD groups, and before and after drying over several years. Drying had stronger effects on taxonomic richness in RD compared to HD networks. In addition, drying greatly altered spatial and temporal β‐diversity in RD networks, but it marginally affected β‐diversity in HD networks. Communities of HD networks showed a higher proportion of resistant taxa than RD networks. These results suggest that recent drying can have, at least on a short time scale (i.e. years), stronger effects on aquatic communities in RD networks compared to those in HD networks. Because drying duration, frequency, and spatial extent are increasing with climate change, RD networks could soon reach tipping points, calling for long‐term monitoring of biodiversity in these novel ecosystems.